Tính toán cấu trúc và động lực của phức Oseltamivir (Tamiflu) với hemagglutin-neuraminidase từ virus cúm người typ III - Mi, Nguyễn Hoạ; Vận, Đặng Ứng (Vietnam Journal of Chemistry, 2012)
We report molecular dynamics calculations of enzyme Hemagglutinin- Neuramidase from human parainfluenza virus type III in complex with inhibitors Zanamivir and Oseltamivir. Computational analysis indicates high stability of these complexes in dynamic equilibrium conditions. Whilst Oseltamivir has more averaged number of hydrogen bonds, more hydrophobic, less hydrophilic surfaces, much higher solvation free energy and more salt bridge created between ligand and protein, Oseltamivir’s IC50 is much higher than Zanamivir one. Besides it there are much more atomic distances of < 0.35nm between Zanamivir and protein than between Oseltamivir and protein. It means that the inhibition activity of Zanamivir is caused by a similarity of its molecular geometry and binding pocket which could make Zanamivir enter more closely the bottom of binding site than Oseltamivir.